Pregled gozdnih združb Slovenije: učbenik za izbirni predmet za 2. in 3. letnik na dodiplomskem študiju Ekologija z naravovarstvom na Fakulteti za naravoslovje in matematiko Univerze v Mariboru - Čarni, Andraž (2019)
Overview of Forest Communities in Slovenia: a Textbook for Students of Ecology with Nature Conservation at the University of Maribor, Faculty of Natural Sciences and Matematics. The textbook The overview of communities forest Slovenia is written particulary for students of the study program Ecology with Nature Conservation, who will choose this course in undergraduate studies. In the first part, the textbook deals with the theoretical bases of elaboration and describing of vegetation in accordance with the Central European method, which enables students to understand the second part, where an overview of the forest vegetation of Slovenia is given. An overview of forest communities is based on a comprehensive database that enables the identification of diagnostic plant species based on calculation of fidelity to a particular vegetation type. The textbook is intended primarily for the students of the indicated course, and it is also useful for other courses, which deal with the research of vegetation and knowledge of forests.
Keywords: vegetation; forests; Central European method; Slovenia; textbook